Historic Preservation as a Tool for Sustainable Community Development - Ellis, S. Peyton (Consilience, 2019)
Although the fields of community development and historic preservation are independently successful, there is an increasing need for professionals from each field to collaborate for efficient urban development. By combining the community building aspects of community development and the sustainable practices of historic preservation, urban development endeavors become more sustainable for both the environment and the people in urban communities. The growing pertinence of both community developers and historic preservationists in urban development is shown through analysis of the practices of each field and case studies involving their collaboration.